Teaching Reading Narrative Text through Story Glovesto the Eighth Grade Students of State Senior High School 7 of Palembang - Eka Dian Aryani; Ferri Hidayad; M Ali Akbar Zam (Universitas PGRI Palembang, 2018)
AbstractThe aim of this study was to find out whether or not the use of story gloves could increase students’ ability in reading narrative text. The writer used cluster random sampling to select the sample. The sample of this study was the 8.1 students of State Junior High School 7 of Palembang. The data were collected by using test. Then, toanalyze the data, the writer used matched t-test. The result showed that story gloves could increase students’ ability in reading narrative text because there was difference students’ score between pre-test and post test. The students’ average score in the pretest was 78,8 and the students’ average score in the post test was 86,8. Finally, theresult of matched t-test calculation was 9.638 and the degree of freedom (df) 39, t-table was 1.697. The t-obtained is higher than t-table, it means that alternative hypothesis was accepted and null hypothesis was rejected. In other word, it was effective teaching reading narrative text through story gloves to the eighth grade students of State Junior High School 7 of Palembang.Keywords: Teaching Reading, Narrative Text, Story Gloves